Who Eats School Breakfast? Parent Perceptions of School Breakfast in a State With Very Low Participation. (14th January 2018) - Spruance, Lori A.; Harrison, Caleb; Brady, Patrick; Woolford, Marti; LeBlanc, Heidi
ABSTRACT: BACKGROUND: Having breakfast is correlated with health and academic benefits; yet, many children do not consume breakfast, and participation in the federal School Breakfast Program remains low. The purpose of this study was to examine parent perceptions of school breakfast and identify relationships between those who consume breakfast at school and those who do not. METHODS: A random sample of 100 schools, representing 29 school districts, across the state of Utah was selected to participate in the survey. Administrators were asked to distribute an online survey link to the parents of their school. Parents answered questions about their oldest kindergarten through 12th grade child. Qualitative and quantitative analyses were performed. RESULTS: A total of 488 parents completed the survey. In a multilevel model, child grade level, participation in free and reduced‐price lunch, and perceive benefits to school breakfast were significantly related to eating breakfast at school. Some major themes from the qualitative analysis included no need for school breakfast, perception of regional values, and logistical issues. CONCLUSIONS: Parent perception of school meals is related to participation. This study identifies several areas of perception that could be address through parent education to increase school breakfast participation.